Kelimpahan Dan Keanekaragaman Ikan Karang Pada Lokasi Transplantasi Karang Di Pantai Harlem Teluk Depapre Kabupaten Jayapura - Paulangan, Yunus Pajanjan; Wally, Alex Ricko (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Coral transplantation is a method of planting and growing a coral colony using the fragmentation method with the aim of accelerating the regeneration of damaged coral reefs, or as a way to improve the coral reef ecosystem. The aim of this research is to determine the abundance and diversity of coral fish in the transplant area which was carried out by the Center for Marine Resources and Fisheries Studies in collaboration with PT. PLN (Persero) Main Unit for Papua and West Papua Regions on Harlem Beach, Tablasufa Village. Data collection on reef fish was carried out using the underwater visual census method. The abundance of reef fish analyzed was a group of major fish, indicator fish and target fish, and the Diversity Index used Shannon-Wiener. Based on the research results, there were 437 reef fish found in monitoring I and 589 reef fish in monitoring II with a total of 35 species from 10 families dominated by major fish groups, namely around 82.52-88.56%, and target fish. which is around 10.98-17.15%. The highest abundance of individual reef fish was found in Monitoring II. This shows that the number of reef fish presence is increasing. On the one hand, higher diversity was found in monitoring I, namely 2.00 than monitoring II, namely 1.90. Based on the Shannon-Wiener category, the diversity index is categorized as moderate. This diversity index is thought to be because transplantation has not been effective in functioning as a habitat for reef fish, as indicated by the very low presence of indicator fish, namely only around 0.34-0.46%. The research results show that coral transplantation has had a positive impact on improving reef fish habitat and coral reef ecosystems.